Development of a homeolog-specific gene editing system in an evolutionary model for the study of polyploidy in nature - Shan, Shengchen; Pisias, Michael T.; Mavrodiev, Evgeny V.; Spoelhof, Jonathan P.; Hauser, Bernard A.; Barbazuk, W. Brad; Soltis, Pamela S.; Soltis, Douglas E.; Yang, Bing (Frontiers in Genome Editing, 2025)
Polyploidy, or whole-genome duplication (WGD), is a significant evolutionary force. Following allopolyploidy, duplicate gene copies (homeologs) have divergent evolutionary trajectories: some genes are preferentially retained in duplicate, while others tend to revert to single-copy status. Examining the effect of homeolog loss (i.e., changes in gene dosage) on associated phenotypes is essential for unraveling the genetic mechanisms underlying polyploid genome evolution. However, homeolog-specific editing has been demonstrated in only a few crop species and remains unexplored beyond agricultural applications. Tragopogon (Asteraceae) includes an evolutionary model system for studying the immediate consequences of polyploidy in nature. In this study, we developed a CRISPR-mediated homeolog-specific editing platform in allotetraploid T. mirus. Using the MYB10 and DFR genes as examples, we successfully knocked out the targeted homeolog in T. mirus (4x) without editing the other homeolog (i.e., no off-target events). The editing efficiencies, defined as the percentage of plants with at least one allele of the targeted homeolog modified, were 35.7% and 45.5% for MYB10 and DFR, respectively. Biallelic modification of the targeted homeolog occurred in the T0 generation. These results demonstrate the robustness of homeolog-specific editing in polyploid Tragopogon, laying the foundation for future studies of genome evolution following WGD in nature.